Survey of lower urinary tract symptoms in United States women using the new lower urinary tract dysfunction research Network‐Symptom Index 29 (LURN‐SI‐29) and a national research registry. Issue 2 (15th January 2022) - Smith, Ariana L.; Chen, Jingwen; Wyman, Jean F.; Newman, Diane K.; Berry, Amanda; Schmitz, Kathryn; Stapleton, Ann E.; Klusaritz, Heather; Lin, George; Stambakio, Hanna; Sutcliffe, Siobhan
Abstract: Purpose: An online bladder health survey was administered to national registry volunteers to: (1) determine the feasibility of using ResearchMatch for studying lower urinary tract symptoms (LUTS); (2) pilot the new, comprehensive Lower Urinary Tract Dysfunction Research Network Symptom Index‐29 (LURN‐SI‐29) and determine its ability to detect known associations with LUTS; and (3) explore novel areas of bladder health in community‐based women. Methods: A cross‐sectional web‐based survey was administered to a random sample of ResearchMatch adult female, transgender and non‐binary volunteers. Participant demographics, health characteristics, the LURN‐SI‐29, and LUTS‐related experiences were collected. Results: A total of 1725 ReseachMatch volunteers with a mean age of 44.0 years completed the study and were eligible for the analysis. Participants were primarily white, cisgendered, highly educated, nulliparous, and premenopausal. The median LURN‐SI‐29 score was 17 (interquartile range: 11–26). More than half the sample reported urinary urgency (71.0%), nocturia (65.7%), and stress incontinence (52.3%) a "few times" or more in the last 7 days. Approximately half reported sensation of incomplete bladder emptying (49.6%) with one‐third reporting urgency incontinence (37.6%); notably, 52.6% of respondents reported being at least "somewhat" bothered by LUTS. LURN‐SI‐29 scores increased with age, body mass index, decrements in self‐reported health, medical comorbidity, parity, menopausal status, and urinary symptom bother, providing evidence of convergent validity. LURN‐SI‐29 scores varied by race and education, with the lowest scores in Asian and highly educated women. Conclusion: Overall, the prevalence and spectrum of LUTS in an online research registry of women volunteers were high and comparable to other population‐based samples. The new LURN‐SI‐29 demonstrated its ability to detect expected associations with demographic and health characteristics in a nonclinical population.